Development of dual-purpose disc agrochemical applicator for field crops - Abubakar, Mohammed Shu'aibu (2011)
The thesis focuses on design, fabrication, development and evaluation of a new dual-purpose disc agrochemical applicator for field crop to boost agricultural mechanization in food production and also to overcome the safety concern of hazardous spray drift from hydraulic nozzles during chemical application by the farmers. Small and large scale models of the new concept dual-purpose agrochemical applicator were successfully developed and evaluated. The small scale equipment was driven by variable rate DC motor and rheostat for disc rotary speed variation. The full scale model (for real application) was propelled by PTO shaft of a high clearance tractor using a step-up gear box for disc speed variation. The dual-purpose equipment’s performances for both granular and liquid chemical application were reported. The performance of the equipment is highly dependent on some physical properties of the chemical to be applied such as density, coefficient of friction, size distribution, viscosity, surface tension as well as prevailing weather conditions like air temperature and humidity. However, the effects of these physical properties were not reported in this study. The dual-purpose agrochemical applicator was tested at application rates of 40 (low), 80 (median) and 120 kg/ha (high) as well as 50 (low), 100 (median) and 150 kg/ha (high) for the urea and NPK granular chemical fertilizers respectively. Rotary disc speed was varied at four different levels 550, 700, 850 and 1000 rpm with three different combinations of 2, 4 and 6-vane disc. Result suggests that the best granular distribution coefficient of uniformity (CUG) of 18% and 19% were achieved at median application rates 40 kg/ha and 50 kg/ha at 550 rpm disc speed and with 2-vane disc for urea and NPK respectively. The worst CUG was obtained at 1000 rpm disc speed combined with 6-vane disc for the both fertilizers. An optimum average working width of 1.8 and 2.1 m in correspondence with CUG values of 18 and 19% for urea and NPK granular fertilizer respectively were achieved. HC amine 48 and NASA glyphosate liquid chemical solutions were each tested at application rates of 30 (low), 60 (median) and 90 l/ha (high) at four different rotary disc speeds of 2000, 3000, 4000 and 5000 rpm with three different diameter discs of 300, 400, 500 mm. Result shows that the average values of volume median diameter (VMD) range from 342-102 µm and 344-108 µm at 2000-5000 rpm rotational disc speed at different values of application rate for NASA glyphosate and HC amine 48 liquid chemicals respectively. The average value of the number median diameter (NMD) varies from 86 to 208 µm and 82 to 209 µm for NASA glyphosate and HC amine 48 liquid solution respectively. These values were determined in order to ascertain the liquid solution spray characteristics. The average values for coefficient of uniformity of the droplet spectrum (CUL) expressed as VMD/NMD were found to be in the range from 1.25 to 1.63 and 1.22 to 1.65 for NASA glyphosate and HC amine 48 liquid chemicals respectively. A comparison in terms of liquid chemical solution deposition between the new developed dual-purpose rotary disc chemical applicator and the results of commonly used conventional knapsack sprayer with flat fan pressure nozzles reported from literatures showed that the latter when operating at a disc speed of 5000 rpm and application rate of 90 l/ha was found to produce spray droplet size of 79% ranging 100-250 µm compared to reported results of former with droplet size of 80% ranging 250-350 µm. This indicates that the new concern application method can produce a narrower range of droplet size than the conventional hydraulic nozzles methods. Also liquid chemical application techniques producing larger droplets size may have unexpected application efficiency and environmental pollution. Lastly, results from the field experimental tests suggest that the average effective field capacity for the equipment on a prime mover was found to be 0.89 ha/hr or 7.12 ha/man-day for a 8 hour working day, when compared with the motorized mistblower knapsack sprayer and conventional knapsack sprayer with 0.35 ha/hr (2.8 ha/man-day) and 0.20 ha/hr (1.6 ha/man-day) respectively. This shows 4 and 6 times lower than when the new developed equipment was used for chemical application instead of motorized mistblower knapsack sprayer and conventional knapsack sprayer respectively. A benefit of an operational cost saving of RM7.7/ha (USD2.6/ha) and RM12.5/ha (USD4.2/ha) were revealed by using the new developed equipment as compared with the use of motorized mistblower knapsack sprayer and conventional knapsack sprayer respectively.